First in CIS systems of metal bottom purging by inert gases in arc steel-melting furnace - M. P. Guljaev; V. V. Filippov; I. V. Ivanov; V. V. Enders; Ev. Shumacher; Ed. Shumacher; R. Franzki; X. Brener (Литьë и металлургия, 2001)
Systems of “direct” and “hidden” types of bottom^ purging of metal by inert gases in a powerful arc steel-melting furnace are investigated and implemented. The given investigations established positive influence of flux composition, mixing and preparation during processing of dispersion and oxidized wastes of aluminum alloys in short-flame rotary furnace. Substitution of cryolite in chlorine-containing flux with fluorspar is proved advisable.